EXPANSION OF SRNS FIELD USING ADS-B GROUND STATIONS - I. N. Shestakov; G. A. Kryzhanovskij (Научный вестник МГТУ ГА)
Method of objects’ positioning in SRNS field with the help of ADS-B ground stations signals is suggested. Such method makes it possible to solve positioning tasks in areas with incomplete GPS covering, for the cases with poorly specified systems, with insufficient accuracy of coordinate identification and so on .